2021
DOI: 10.1210/jendso/bvab090
|View full text |Cite
|
Sign up to set email alerts
|

Spine Bone Texture Assessed by Trabecular Bone Score in Active and Controlled Acromegaly: A Prospective Study

Abstract: Purpose Acromegalic patients have an increased vertebral fracture (VFx) risk due to bone quality reduction, independently of bone mineral density (BMD). Aim of the study is to describe bone quality in acromegaly, measured by Trabecular bone score (TBS), a non-invasive index for assessing bone microarchitecture. Methods We collected data of 18 patients (13 F, age 56.2±15 years) newly diagnosed with acromegaly. Thirty-six age-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…They observed the decrease of TBS and the increase of BMD following the treatment ( 13 ). On the contrary, in the recent study, no TBS and BMD variation was observed 1 year after the biochemical cure or control of the acromegaly disease ( 30 ).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…They observed the decrease of TBS and the increase of BMD following the treatment ( 13 ). On the contrary, in the recent study, no TBS and BMD variation was observed 1 year after the biochemical cure or control of the acromegaly disease ( 30 ).…”
Section: Discussionmentioning
confidence: 70%
“…We did not observe the correlation between TBS as well as BMD and bone markers (NTX and OC concentrations). In some previous studies, an increase of bone turnover markers (OC and CTX-1) in AGs compared to controls ( 10 , 30 ) or CA ( 39 ) was demonstrated, but they also did not find the correlation between these markers and BMD ( 10 ). Moreover, taking into account the fact that only 15% of OC is detected in the circulation, and that the characteristic feature of this non-collagenic protein is the high concentration variation in the circadian secretion profile (up to 30%) ( 40 ), this could have influenced the results obtained in our study and, as a result, the lack of significant differences in the concentration of OC between the groups.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, Calatayud and colleagues reported higher TBS values in patients who underwent post-surgical remission [ 43 ], while a previous report from Godang K et al described a reduction in TBS values one year after surgery, although associated with an increase in BMD levels [ 24 ]. Recently, Sala and colleagues failed to demonstrate significant changes in both TBS and BMD values in a prospective study evaluating 18 acromegalic patients at diagnosis and 12 months after achieving cured/controlled disease (66.7% of the patients were treated with somatostatin receptor ligands) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, few studies have analyzed TBS in patients with acromegaly [ 23 , 24 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In most cases, the authors reported lower TBS values in acromegalic patients compared to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%